Revisiting the exposure criterion for PTSD: Using the COVID-19 pandemic as an opportunity to assess measurement invariance of PTSD symptoms across event types - Anouk van Duinkerken; Peter G. van der Velden; Michel L. A. Dückers; Christos Baliatsas; Mark W. G. Bosmans (PLoS ONE, 2026)
Introduction There is an ongoing debate about the exposure criterion of PTSD since its introduction in the DSM-III in 1980 and the global COVID-19 pandemic has fueled it. Studies examining the prevalence of PTSD following the COVID-19 pandemic are criticized because assessed stressful pandemic-related events do not fulfill the exposure criterion of the DSM-5 and ICD-11. However, if stressful pandemic-related events are indeed distinct events compared to events that fulfill the exposure criterion, measurement noninvariance of PTSD symptom clusters should occur. The aim of the present study is to test this hypothesis. Methods For this purpose data from the Dutch Public Health Monitor 2022, based on a large random sample of the Dutch population (n = 72,851) was extracted. We examined the measurement invariance in the PCL-5 subscales across different categories of events that people have experienced during the pandemic, such as the sudden hospitalization of a loved one and not being able to say goodbye to a loved one who passed away due to COVID-19. Results The mean PCL-5 score was 12.36. PTSD prevalence was 9.74%, higher for events fulfilling the DSM-5 exposure criterion (16.54% vs. 9.05%), with smaller difference between events fulfilling the ICD-11 exposure criterion. Model fit was acceptable across all event categories. Multigroup analyses showed that constraining loadings, intercepts, and error variances did not meaningfully worsen fit, changes in CFI and RMSEA remained below thresholds, supporting measurement invariance across event types. Conclusions: The results show measurement invariance between events during the pandemic that did and that did not comply with the DSM-5 or ICD-11 exposure criterion. These results suggest that the current exposure criteria in the DSM-5 and ICD-11 may not capture all relevant events and underscore the importance of further research to guide potential updates.